Coffee culture: Gen Z and coffee shops - Azahra, Ditha Arditia; Apriliani, Zahra Arni; Muabdan, Muabdan; Khumayah, Siti; Wulandari, Sri (International Journal Labs, 2024)
The provision of restitution to victims of criminal acts is considered not optimal in its implementation with various problems such as from the regulatory aspect and at the level of implementing relevant stakeholders in the implementation of prosecutions. The results of this study will be presented by describing the data obtained through literature studies analyzed by quantitative methods. The study shows that there is a need for an arrangement that contains a substitute crime if the defendant or convicted person is not able to pay a replacement crime as a norm that becomes the legal basis for public prosecutors and judges in prosecuting and deciding cases. The problem arises due to the lack of comprehensive regulations regarding criminal charges in lieu of the payment of compensation, the non-regulation of criminal substitutes for the payment, and the nonregulation of the amount of the criminal substitute. The ideal arrangement in a criminal prosecution that is carried out comprehensively and correctly by the relevant parties is expected to provide legal certainty, justice, and expediency.